Study of Haematological and Cardiovascular Parameters in Relation to Blood Lead Levels in Spray Painters and Welders (International Journal of Physiology, 2019)
BackgroundOccupational exposure to lead is most common in preparation of lead containing paint, welding etc. Lead poisoning is one of the compensable diseases in India since 1924. causes negative effects particularly on nervous, cardiovascular, renal, hepatic and hematopoietic system.ObjectiveTo assess haematological and cardiovascular parameters in relation to blood lead levels in spray painters and welders.Method and MaterialStudy group included 455 male painters and welders working in small industries for two to six years. Age and gender matched controls were selected. Study was carried out in the private laboratory in Bangalore. Blood lead levels (BLL), Haematological parameters like Red blood cell count(RBC), Haemoglobin concentration (Hb), Reticulocyte count, Blood indices were estimated using an auto analyzer and Blood pressure was recorded during their workshift.ResultsThe mean BLL of study group was 1.988±0.312 ?g/dL, compared to control group which was 1.77±0.2865 ?g/dL (t= 16.82, p = 0. 612). Study group, showed 36 workers with high BLL (?10 ?g/dL). No correlation was found between anaemia and hypertension and BLL.ConclusionMean of BLL in study group was not statistically significant compared to control group. Low lead exposure rates and efficient institutional and/or personal protective measures may be the reason behind this outcome.